2015
DOI: 10.1142/s136391961540006x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Employee Knowledge Risks in Multinational, Multilevel Organisations: Managing Knowledge Leaking and Leaving

Abstract: Maintaining innovation potential means that ideas, and the people generating those ideas, should be at the firms disposal. Furthermore, the firm should be able to capture value from people's ideas. Losing these people therefore poses risks. Managing these risks is challenging, especially without intra-firm consensus on their role. This study examines how and why perceptions of severity and management of risks related to knowledge leaving and knowledge leaking differ across organisational levels and different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our results support that understanding employee behavior is important for examining why business-critical knowledge leaks and how it can be protected (Baughn et al ., 1997; Hannah and Robertson, 2015); accordingly, the results respond to the calls for research into the roles of individuals in the knowledge sharing interface (Foss et al ., 2010; Ghosn and Rosenkopf, 2015; Salter et al ., 2015). For instance, research has shown that the employees’ acknowledgment and willingness to follow guidance on these issues can vary (Olander and Hurmelinna-Laukkanen, 2015), and they might bend rules for the sake of good collaboration (Hannah and Robertson, 2015), which could have critical effects in terms of leakage if they do not use good judgment. As we have shown, this problem is especially relevant for firms pursuing radical innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support that understanding employee behavior is important for examining why business-critical knowledge leaks and how it can be protected (Baughn et al ., 1997; Hannah and Robertson, 2015); accordingly, the results respond to the calls for research into the roles of individuals in the knowledge sharing interface (Foss et al ., 2010; Ghosn and Rosenkopf, 2015; Salter et al ., 2015). For instance, research has shown that the employees’ acknowledgment and willingness to follow guidance on these issues can vary (Olander and Hurmelinna-Laukkanen, 2015), and they might bend rules for the sake of good collaboration (Hannah and Robertson, 2015), which could have critical effects in terms of leakage if they do not use good judgment. As we have shown, this problem is especially relevant for firms pursuing radical innovations.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that addressing the knowledge leaving risk through proactive HRM practices is essential. This is especially important since reactive HRM practices in general do not seem to work particularly well in preparing for leaving risks (but rather work for knowledge leakages; see e.g., Liebeskind, 1996;1997;Bulgurcu, 2010;Hurmelinna-Laukkanen et al, 2015). In the following we will elaborate on the finding regarding trustworthiness and commitment in more detail.…”
Section: Methodsmentioning
confidence: 97%
“…While different mechanisms are available to deal with these aspects, the HRM-related mechanisms have high potential in producing expected outcomes in balancing knowledge protection and sharing (Rousseau and Wade-Benzoni, 1994;Liebeskind, 1996Liebeskind, , 1997Hurmelinna-Laukkanen et al, 2015;Norman, 2001, Norman, 2002. Bulgurcu et al, (2010), Hannah and Robertson (2015) and Liebeskind (1996Liebeskind ( , 1997, Olander and Hurmelinna-Laukkanen (2015) among others, address some HRM-related mechanisms that may ease the problem with knowledge leaving and leaking. These can be categorised according to their formality, for example (Olander et al, 2014), but also according to the phase in which they are applied, and where (geographically and culturally) they are most suitable (Olander and Hurmelinna-Laukkanen, in press).…”
Section: Knowledge Leaving and Leaking Risks Inducing Need For Proactive Approach To Knowledge Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging CC in the NPD process also increases the risk of knowledge misappropriation. Customers and employees involved in the collaborative innovation process may leak sensitive information into the public domain unintentionally due to unawareness of its confidentiality, overenthusiasm in problem solving, and/or mistakes (e.g., leaving documents unattended) (Matusik and Hill 1998; Olander and Hurmelinna-Laukkanen 2015). Knowledge leakage can also occur when customers who disregard confidentiality clauses leak secrets to other firms intentionally for personal gain.…”
Section: Theoretical Frameworkmentioning
confidence: 99%